Single-Source Gravitational Wave Limits From the J1713+0747 24-hr Global Campaign. (May 2016) - Dolch, T.; Ellis, J. A.; Chatterjee, S.; Cordes, J. M.; Lam, M. T.; Bassa, C.; Bhattacharyya, B.; Champion, D. J.; Cognard, I.; Crowter, K.; Demorest, P. B.; Hessels, J. W. T.; et al.
Abstract: Dense, continuous pulsar timing observations over a 24-hr period provide a method for probing intermediate gravitational wave (GW) frequencies from 10 microhertz to 20 millihertz. The European Pulsar Timing Array (EPTA), the North American Nanohertz Observatory for Gravitational Waves (NANOGrav), the Parkes Pulsar Timing Array (PPTA), and the combined International Pulsar Timing Array (IPTA) all use millisecond pulsar observations to detect or constrain GWs typically at nanohertz frequencies. In the case of the IPTA's nine-telescope 24-Hour Global Campaign on millisecond pulsar J1713+0747, GW limits in the intermediate frequency regime can be produced. The negligible change in dispersion measure during the observation minimizes red noise in the timing residuals, constraining any contributions from GWs due to individual sources. At 10 -5 Hz, the 95% upper limit on strain is 10 -11 for GW sources in the pulsar's direction.